Management Of Damping Off And Improvement Of Growth In Chilli With Native Species Of Arbuscular Mycorrhizae - Kavitha K (Department of Plant Pathology, College of Agriculture, 2001)
Management of damping off, the most destructive disease of chilli both 111 nursery and main field incited by Pythium aphanidermatum (Edson) Fitz. using native AMF was attempted in the present investigation. Out of nine native AMF and one identified culture (Glomus mosseae) screened, the cultures Ms and M9 were found effective for suppression of damping off and growth improvement in chilli. Application of AMF inoculum in the nursery furrows along with chilli seeds was very effective for rapid and easy colonization of AMF. Likewise application of AMF inoculum at the rate of 850 g m-2 was selected as the economic dose for achieving satisfactory colonization of AMF. Azospirillum spp. were isolated from chilli roots collected from different locations of Thiruvananthapuram district. The in vitro nitrogen fixing capacity of the isolates ranged between 11.2 and 20 mg N s' of malate and IAA production between 21 and 55 ug mrl. Six best isolates which performed well under in vitro screening were selected an-d subjected to in vivo screening for growth, biomass production and yield in chilli. The isolates Az-l and Az-2 which performed well both under in vitro and in vivo screening were selected for further studies. Based on the characterization studies it was found that the isolate Az-l is related to Azospirillum lipoJerum and Az-2 is similar to Azospirillum brasilense. The isolate Az-l grew well at pH 5,6 and 7 whereas the isolate Az-2 grew well at pH 6 and 7.